Continuous Normothermic Machine Perfusion for Renovation of Extended Criteria Donor Livers Without Recooling in Liver Transplantation: A Pilot Experience - Chen, Zhitao; Hong, Xitao; Huang, Shanzhou; Wang, Tielong; Ma, Yihao; Guo, Yiwen; Huang, Changjun; Zhao, Qiang; Guo, Zhiyong; He, Xiaoshun; Ju, Weiqiang; Chen, Maogen (Frontiers in Surgery, 2021)
Background: Ischemia injury affects the recovery of liver allograft function. We propose a novel technique aimed at avoiding a second ischemic injury: transplanting an extended criteria donor (ECD) liver directly under normothermic machine perfusion (NMP) without recooling. We studied two cases to evaluate the efficacy and safety of this technique. Methods: The perioperative characteristics and postoperative outcomes of two recipients of ECD livers were analyzed. Both transplantations were performed with continuous normothermic machine perfusion without recooling. Result: In case 1, the cause of donor death was anoxia, and the donor liver had hypernatremia before procurement. The recipient was diagnosed with decompensated cirrhosis. His model for end-stage liver disease (MELD) score was 38. In case 2, the donor liver was from a donor after cardiac death (DCD), and the donor had elevated aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels. The recipient was diagnosed with acute hepatic failure. His MELD score was 35. Both donor livers were maintained under NMP and then transplanted without recooling. The peak ALT and AST levels after surgery were 452 and 770 U/L in case 1 and 100 and 592 U/L in case 2. Neither early allograft dysfunction (EAD) nor primary graft non-function (PNF) was present in these two cases. Conclusion: In conclusion, our results demonstrate that continuous NMP without recooling is efficacious and safe for LT with extended criteria donor livers. Further investigations of this technique will be performed to confirm these promising results.